If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + (x + 19)(x + 19) = (x + 16)(x + 16) Reorder the terms: 15x + (19 + x)(x + 19) = (x + 16)(x + 16) Reorder the terms: 15x + (19 + x)(19 + x) = (x + 16)(x + 16) Multiply (19 + x) * (19 + x) 15x + (19(19 + x) + x(19 + x)) = (x + 16)(x + 16) 15x + ((19 * 19 + x * 19) + x(19 + x)) = (x + 16)(x + 16) 15x + ((361 + 19x) + x(19 + x)) = (x + 16)(x + 16) 15x + (361 + 19x + (19 * x + x * x)) = (x + 16)(x + 16) 15x + (361 + 19x + (19x + x2)) = (x + 16)(x + 16) Combine like terms: 19x + 19x = 38x 15x + (361 + 38x + x2) = (x + 16)(x + 16) Reorder the terms: 361 + 15x + 38x + x2 = (x + 16)(x + 16) Combine like terms: 15x + 38x = 53x 361 + 53x + x2 = (x + 16)(x + 16) Reorder the terms: 361 + 53x + x2 = (16 + x)(x + 16) Reorder the terms: 361 + 53x + x2 = (16 + x)(16 + x) Multiply (16 + x) * (16 + x) 361 + 53x + x2 = (16(16 + x) + x(16 + x)) 361 + 53x + x2 = ((16 * 16 + x * 16) + x(16 + x)) 361 + 53x + x2 = ((256 + 16x) + x(16 + x)) 361 + 53x + x2 = (256 + 16x + (16 * x + x * x)) 361 + 53x + x2 = (256 + 16x + (16x + x2)) Combine like terms: 16x + 16x = 32x 361 + 53x + x2 = (256 + 32x + x2) Add '-1x2' to each side of the equation. 361 + 53x + x2 + -1x2 = 256 + 32x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 361 + 53x + 0 = 256 + 32x + x2 + -1x2 361 + 53x = 256 + 32x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 361 + 53x = 256 + 32x + 0 361 + 53x = 256 + 32x Solving 361 + 53x = 256 + 32x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-32x' to each side of the equation. 361 + 53x + -32x = 256 + 32x + -32x Combine like terms: 53x + -32x = 21x 361 + 21x = 256 + 32x + -32x Combine like terms: 32x + -32x = 0 361 + 21x = 256 + 0 361 + 21x = 256 Add '-361' to each side of the equation. 361 + -361 + 21x = 256 + -361 Combine like terms: 361 + -361 = 0 0 + 21x = 256 + -361 21x = 256 + -361 Combine like terms: 256 + -361 = -105 21x = -105 Divide each side by '21'. x = -5 Simplifying x = -5
| 53d*602=1 | | x^3+8x+9=0 | | 6+5(x-8)=10x | | m+5n^2=0 | | 16-4(x-7)=3x-12 | | t^2-t-380=0 | | X^2-6x-5=-8 | | 123-x=12 | | X+x-29+x+20=180 | | 6xy+xy+2yx= | | 8x+3y=-10 | | 12x^4/18x^3 | | f(x)=3.4 | | =5t^2+3t^3 | | .0027=(.5)(9.8)(x^2) | | f(x)=5t^2+3t^3 | | lg(x^2-3x)=lg(3x-8) | | (x^2)+ax-(2a^2)=0 | | 6a+10a+3a= | | 5xyz=a | | 10a-2b-a-b=0 | | .4x-.6x-2=-2 | | .04x-.06x-2=-2 | | 5h=2x-35 | | 3-3sinx= | | x+3.6=4.6 | | 12x-9(-6)=6 | | 36-2w=80-3e | | x+x+8-3x=4x-2 | | X+x+8-3=4x-2 |